2013
DOI: 10.3892/etm.2013.1156
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and multimodal therapy for extragastrointestinal stromal tumor of the prostate: A case report

Abstract: Extragastrointestinal stromal tumors (EGISTs), which are neoplasms outside the digestive tract, are predominantly observed in the greater omentum and retroperitoneum. The clinicopathological and molecular characteristics of EGISTs are similar to those of gastrointestinal stromal tumors (GISTs). EGISTs originating from the prostate are extremely rare. In this study, we report a case of a prostatic EGIST in a 39-year-old male, who presented with frequency, urgency, dysuria and a prostatic mass. A 10-core transre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…Most of the published studies reported six cases of primary prostatic GIST [4][5][6][7][8][9]. However, deep digging revealed more cases [10][11][12][13][14][15][16]; all are listed in Table 1. Cases that were excluded from our study were extraperitoneal, rectovesical, and retroprostatic masses [17] and masses between the rectum and prostate [18] or contiguous to rectal wall [19].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the published studies reported six cases of primary prostatic GIST [4][5][6][7][8][9]. However, deep digging revealed more cases [10][11][12][13][14][15][16]; all are listed in Table 1. Cases that were excluded from our study were extraperitoneal, rectovesical, and retroprostatic masses [17] and masses between the rectum and prostate [18] or contiguous to rectal wall [19].…”
Section: Resultsmentioning
confidence: 99%
“…There are no characteristic radiographic features, and the mainstay of diagnosis are the histopathological findings along with immunohistochemistry. [134] Majority of the E-GISTs (>95%) express CD117, whereas around 50%–100% express CD34 antigen. [134] In some cases, positive staining for S100 protein, desmin, or smooth muscle actin may also be seen.…”
Section: Discussionmentioning
confidence: 99%
“…[1] E-GISTs of the prostate are rare with less than 10 cases reported in the English literature till date. [123456789] We present the case of a 55-year-old male diagnosed with prostatic E-GIST during workup for lower urinary tract symptoms (LUTS) managed with medical therapy. The present case is the tenth case of prostatic E-GIST.…”
Section: Introductionmentioning
confidence: 99%
“…Other primary sarcomas are extremely uncommon, which also include primary prostatic EGIST along with malignant fibrous histiocytoma, angiosarcoma, osteosarcoma, chondrosarcoma, malignant peripheral nerve sheath tumour and synovial sarcoma. [9] Due to the proximity of prostate with the rectum, the possibility of patients presenting with urinary symptoms from large GIST of rectal origin (due to large volume causing mass effect) should be excluded. Table 1 presents the previously reported cases of EGIST including the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional chemotherapy and radiotherapy are not effective in the treatment of EGISTs. IM, which is [4] 75 6.7 TURP+RP Yinghao et al, 2007 [10] 49 8 RP Ou et al, 2013 [9] 39 10 RP+Imatinib Zhang et al, 2014 [3] 31 6.5 Imatinib Liu et al, 2014 [1] 55 10.5 RP+Imatinib Etit et al, 2017 [8] 56 Table 2]. Similar predictive value was also proposed by Reith et al, for EGISTs in his analysis of 48 patients, according to whom mitotic activity and necrosis have independent predictive value.…”
Section: Discussionmentioning
confidence: 99%